The English Teachers’ Perception Toward English as a Local Content at Elementary School in Tana Toraja. - Theresyam Kabanga' (UKI TORAJA, 2016)
The objective of the research is to know the English teachers’ perception towardEnglish as a local content at Elementary School in Tana Toraja.The writer used qualitative descriptive method and used purposive samplingtechnique. The population in this research was English teachers at the ElementarySchool both public schools and private schools spread in Tana Toraja regency. Thesamples in this research were six English teachers from four schools namely: SDN 214Inpres Kalumpang, SD Kristen Makale 1, SDN 114 Inpres Batupapan dan SDN 215Inpres To’ra’da’. The writer conducted in-depth interview with recording the interviewresult to describe the English teachers’ perception toward English as local content atElementary School in Tana Toraja. Data from the interview result were analyzed usingthe technique: data reduction, data display and conclusion.The result of this research revealed that teachers assume should be introduced atyoung age because it helping students to be up to date by adjusting material accordingto the student level and using many handbooks to fulfill the needs of students as wellas taught by teacher with English education background.Generally, English teachers’ perception is English as a local content atElementary School in Tana Toraja very important. In conclusion, all teachers have thesame perception namely a positive perception toward English as local content in anElementary School in Tana Toraja.